USER INTERFACE AND EXPERIENCE IMPLEMENTATION ANALYSIS ON THE MADRASAH ALIYAH RAUDATUL YATAMA INFORMATION SYSTEM - Muhammad Fajrian Noor; Syarifil Anwar; Sofyar Sofyar; Afief Dzakie Na’imy (UPT Publication and Journal Management, Islamic University of Kalimantan, 2023)
The use of information technology in the field of education aims to make educational organizations or institutions more efficient. One example of information technology in the world of education is building a school information system, one of which is the academic information system for Madrasah Aliyah Raudatul Yatama. Based on the evaluation results of improving the quality of the Raudatul Yatama Madrasah Aliyah information system, the suggestions for improvement that are the focus are the measurement aspects that direct the user interface to a simpler level but have high usability. Because more than half of the respondents stated that the user interface still needs development both in terms of appearance and usability, Therefore, the developer of the Madrasah Aliyah Raudatul Yatama information system can focus more on the aspects included in these criteria for better system quality.